Sleep Quality Among College Students - Elda Irma Jeanne Joice Kawulur; Alfi Khofirotul Janah; Febriza Dwiranti (Jurnal Penelitian Pendidikan IPA, 2023)
Many activities and lecture assignments of student cause students unable to divide their time well. Playing games or social media cause students often sleep late at night, and this has an impact on the disturbance of sleep quality. This study aims to identify the sleep quality of college students at Manokwari West Papua Province. We conducted cross sectional research in male and female students aged of 18-25 years who carry out activities on campus. Sleep quality data was collected through semi-structural interviews using the Pittsburgh Sleep Quality Index (PSQI) questionnaire.Â  Our results showed that most Papua University students had poor sleep quality (78%) in the past 1 month. The sleep quality of girls (48%) were poorer than boys (30%).